Knowledge-Based Collaborative Lean Manufacturing Management (KBCLMM) system - Mohd Nawawi, Mohd Kamal; Khan, Mohammed Khurshid; Hussain, Khalid (Air Force Institute of Technology, Poland, 2008)
The objective of this research paper is to demonstrate the application of hybrid Knowledge-Based System, Gauging Absences of Pre-Requisites (GAP), and Analytic Hierarchy Process (AHP) approaches for selecting the improvement programs for Collaborative Lean Manufacturing Management (CLMM) System.In this research, a generic Knowledge-Based System is developed to measure the level of CLMM adoption in automotive manufacturers compared to the ideal system. Using the embedded GAP and AHP technique, the key lean manufacturing improvement programs can be prioritised by using both qualitative and quantitative criteria.The analysis covers the planning stage of the KBCLMM. The utilisation of the approach is demonstrated with an illustrative example.